ASSESSMENT OF ACROSOMAL INTEGRITY OF DOG SPERMATOZOA USING SPERMAC STAINING TECHNIQUE - UMAMAGESWARl, J; JOSEPH, CECILIA; KULASEKAR, K; KALATHARAN, J; SRIDEVl, P (The Indian Journal of Animal Reproduction, 2023)
Semen was collected by digital manipulation from eighteen matured dogs of three different breeds. Thesperm rich second fraction of semen samples were diluted, cooled and frozen in programmable freezer at threedifferent cooling rates. In an attempt to monitor any changes occurring to the acrosome during freezing, smearsmade with fresh semen and with frozen semen at various cooling rates were stained with spermac stain andexamined under 400x magnifications. Most acrosomal damage appeared to occur during fast and mediumcooling rates than in slow cooling rate of programmable freezing. Further, the use of Spermac stain with slightmodification in staining technique in the present study provides simple and accurate assessment of the acrosomalmembrane changes in frozen thawed dog spermatozoa.
Keywords: Acrosome; Sperrnac stain; Programmable freezing